Influenza D Virus in Domestic and Stray Cats, Northern China, 2024 - Mingshuai Shen; Xinkun Zhao; Jian Zhang; Cun Liu; Chengyi Qi; Ruohan Wang; Jieshi Yu; Kezhou Wang; Zhao Wang (Emerging Infectious Diseases)
Influenza D virus infects primarily cattle, but infrequent reports of infections in cats occur. We detected influenza D virus antibodies in 8 of 360 cats in northern China. Domestic cats showed higher susceptibility than strays. Our results suggest a previously overlooked aspect of epidemiology of this virus in companion animals.